#TITLE_ALTERNATIVE# - PUTU YUNI NURMALASARI (NIM : 10208017); Pembimbing : Prof. Dr. rer. nat. Umar Fauzi, NI
Sedimentation consists of decomposition process, erosion, transportation, deposition, and compaction. Study of sedimentation is a basic step to understand the physical properties of rock such as the porosity. Molecular Dynamics (MD) is a potential method to model sedimentation of granular. There are three important aspects as a basic in molecular dynamics modeling, i.e.: structure, dynamics, and interaction. In modeling level, the scientist needs computational techniques in order to see the dynamics of each particle. Generalized of particle trajectory is the most important aspect in this modeling. Particle trajectory become very important because its contain information about calculation of physical parameters which used in system simulation. In this study, MD was used for modeling the sedimentation of grains. The produced model is 3-D sedimented grains in transparent box-shaped container. The grains follow this two conditions: overlapped and non-overlap. The overlapped condition between the grains describes the nature of sedimentary rock under overpressure that make the grains bounded one another. The non-overlapped condition between the grains describes the condition of very hard grains so the grains not bounded at all. The compaction causes the porosity in rock decreased and also produces smaller radii of pore. Distribution of pore size seems to obey lognormal distribution, usually similar to usual real sedimentary rock. The calculated porosity also linked to porosity vs. depth function, and generally porosity decreased as the depth of sediment layers. This happens because the pressure increasing with number of grains which also increasing in every layer, and compressed rock pore. vii The experiment was also performed to see the change of porosity, pore size distribution, and the relations of porosity vs. depth of sediment layers. Experiment used artificial grains which can represent the overlap and non-overlap condition in sedimentary rock grains.